2022
DOI: 10.1111/cobi.13895
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding why consumers in China switch between wild, farmed, and synthetic bear bile products

Abstract: Article Impact StatementWildlife consumer characteristics and preferences determine their likelihood and direction of switching between legal and illegal products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Regulations were consistently perceived as the most effective approach for interventions targeting TCM practitioners to reduce illegal animal‐based medicine consumption in the first round of co‐design discussion. However, all workshop groups identified consumers as the key target audience for the design of new tailored interventions, as all stakeholders view the importance of changing consumer preferences in shifting demands that affect trade and supply, which is consistent with other research in the illegal wildlife trade context (Hinsley et al, 2022; Thomas‐Walters et al, 2020).…”
Section: Methods and Co‐design Processsupporting
confidence: 74%
See 1 more Smart Citation
“…Regulations were consistently perceived as the most effective approach for interventions targeting TCM practitioners to reduce illegal animal‐based medicine consumption in the first round of co‐design discussion. However, all workshop groups identified consumers as the key target audience for the design of new tailored interventions, as all stakeholders view the importance of changing consumer preferences in shifting demands that affect trade and supply, which is consistent with other research in the illegal wildlife trade context (Hinsley et al, 2022; Thomas‐Walters et al, 2020).…”
Section: Methods and Co‐design Processsupporting
confidence: 74%
“…Regulations were consistently perceived as the most effective approach for interventions targeting TCM practitioners to reduce illegal animal-based medicine consumption in the first round of co-design discussion. However, all workshop groups identified consumers as the key target audience for the design of new tailored interventions, as all stakeholders view the importance of changing consumer preferences in shifting demands that affect trade and supply, which is consistent with other research in the illegal wildlife trade context (Hinsley et al, 2022;Thomas-Walters et al, 2020). This co-design stage is also key to allow participants to reflect on the initial goal and clarify the specific aims of usergenerated ideas, since the initial problem is often defined by experts; this process permits participants' ideas to feature throughout the co-design process .…”
Section: Reflectingsupporting
confidence: 71%
“…Hinsley and Sas-Rolfes (2020) argue that methodological limitations of consumer studies oversimplify consumer behaviour and fail to incorporate the diverse array of factors that influence realworld consumer decisions. Consumers readily switch between wild-caught, captive-bred and synthetic bear bile products depending on the price, production method, perceived effectiveness, safety and legality of the product (Hinsley et al, 2022), with consumer elasticity also being observed regarding the consumption of wild-caught and farmed turtle meat (Nuno et al, 2018).…”
Section: Consumer Attitudesmentioning
confidence: 99%
“…The final design included 18 choice sets, which were randomly distributed into three blocks so that each block contained ). We used the priors from this model to conduct the D-efficient Bayesian design combinations but kept the original basic structure (Dang Vu et al, 2022;Hinsley et al, 2022). Illustrations were included in the choice questionnaire to depict attributes and differentiate among their levels to reduce the cognitive burden of the respondents (Appendix S12).…”
Section: Discrete Choice Experiments and Survey Designmentioning
confidence: 99%